An Econometric lnput-Output Model for Indonesia: Economic lmpact Analysis of Budget Development Expenditure - Hendranata, Anton; Brodjonegoro, Bambang P. S.; Sinaga, Bonar M. (Economics and Finance in Indonesia, 2004)
.